Знахарскія тэксты ў кантэксце традыцыйнай культуры беларускіх татараў - Сынкова, Ірына (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The healing texts of heterogeneous origin are preserved in the manuscripts of the Belarusian Tatars in large numbers. According to written sources, they have been widely used in the past in the Tatar environment. Recent field studies show that the healing texts have not yet completely disappeared from use. These texts have deep roots in the ancient Turkic culture, and also reflect various influences, mainly from the side of Islam, as well as from the Christian-Slavic environment. In general, the healing texts are very interesting sources for analyzing the traditional worldviews of the Belarusian Tatars.